Research of quality indicators of semi-finished turkey meat products prepared using sous-vide technology - F. N. Meretukova; N. V. Abregova (Новые технологии, 2021)
The purpose of the research is to develop a recipe for turkey meat semi-finished product to update the assortment of branded and new dishes in «Minotavr» LLC restaurant chain and restaurants of national cuisine, using modern cooking technologies that maximally preserve meat succulence. New methods and organization of the process of preparing poultry meat dishes using modern technologies and equipment in the restaurants «Maykop» and «Mezdah» have been studied. A recipe for a semi-finished product from turkey meat prepared using the sous-vide technology is presented, including breast meat, thyme, garlic salt (Adygheyskaya), crushed black pepper, butter. The preferences of cooking according to the sous-vide technology in relation to traditional cook- ing, as well as the use of combined types of heat treatment, have been revealed. The technology of semi-finished product production has been considered step by step: incoming control of raw materials and auxiliary materials; preparation of components according to the recipe; fillet cutting into oblong oval plates; preparation of the marinade; pickling raw materials; heat treatment, cooling; quality control and product storage. Evaluation of experimental samples includes the study of physicochemical and organoleptic characteristics. The heat treatment methods used during the study can significantly increase the shelf life of the semi-finished product and improve its taste, while maintaining microbiological purity. The quality characteristics of the finished product, obtained during storage, confirm the declared shelf life. As a result of the research, regulated indicators have been established, such as shelf life of semi-finished turkey meat no more than 7 days; storage temperature 4±2 °С.